Use of an Autologous Bone Graft Derived from Three Caudal Vertebrae for Reconstruction in a Dog with Radioulnar Atrophic Nonunion and Osteomyelitis - Goto, Masato; Ikeda, Hitoshi (VCOT Open, 2022)
This case report describes the case of a 4-year-old toy poodle who underwent reconstruction using an autologous caudal vertebral graft for nonunion and osteomyelitis of a left radioulnar fracture. Radial reconstruction was performed 14 days after the removal of existing implants. Three autologous caudal vertebrae mounted onto a titanium T-plate were used to fill the radial bone defect. Rehabilitation was initiated 3 weeks after surgery. By the fifth week after surgery, the dog showed weight bearing on the affected limb. One year after the reconstruction surgery, revision surgery for replacing all implants was performed due to increased radiolucency of the graft. The dog remained clinically stable, and radiographic bone union was complete 3 years and 2 months after the first surgery. An autologous caudal vertebral graft was successfully used for the treatment of a large radial defect in a dog suffering from atrophic nonunion. Clinical improvement was prompt, and the long-term functional outcome was satisfactory.
Keywords: vertebrae graft; large bone gaps; nonunion